Response of Tobacco Farmer to PMUP (Participative Model of Farming Activity) in Tlahab Village, Kecamatan Kledung, Kabupaten Temanggung - Arfianto, Andrie (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Agricultural sustainable development is an integrated effort to support agricultural activities by involving stakeholders with different backgrounds and motives; such as social, cultural, economic, and environmental. Participatory Farming Model Development (Pengembangan Model Usahatani Partisipatif â€ PMUP) conducted by the government in Desa Tlahab intended to improve the farmerÂ welfare by increasing income without sacrificing the heritage of tobacco farming culture whileÂ reducing the environmental damage caused by tobacco cultivation. This kind of agriculturalÂ activities need immense participation and willingness of the farmers as a supporting response forÂ the implementation of this system on their land. Farmers stated that living conditions have keptÂ them from supporting the implementation of PMUP. This condition includes farmer socioâ€economicÂ situation, environmental conditions in carrying out the activities, the low performance of farmerÂ groups, lack of competitiveness of the PMUP compared to previous agricultural system, also lack ofÂ performance from the institutional boards.